A good night’s sleep: A narrative review from the prespective of Islam and modern sciences - Mohamad Noor, Zaswiza; Yusof, Nurul Nabilah; Fakhrul Ruzi, Fasiha Ruhila; Sanusi, Nurul Atiqah (2016)
Introduction: As a biological universal, it is easy to overlook the degree to which culture and religion shape how people sleep, with whom, where and when, and how quality sleep is conceptualized. In Western world, sleep hygiene tips to get “good night’s sleep” are usually focusing on maintaining body’s natural rhythms, controlling exposure to light, getting regular exercise and controlling types of food and drink. Meanwhile, sleep medicine is also considered an important issue from Islamic perspective, which, the Quran and Hadith discuss types of sleep, the importance of sleep and good sleep practices. Types of sleep as described, are corresponded with sleep stages identified by modern sciences, as well as the beneficial effects of sleep and the importance to maintain a pattern of light and darkness. In modern sciences, sleep deprivation is regarded as significant health issue which usually due to inadequate sleeping time. However from Islamic point of view, long sleep hours alone does not determine the efficiency of sleep, but rather it depend on various other factors and following the sleeping etiquettes of prophet Muhammad (SAW) is proposed as the best solution to acquire quality sleep. Objectives: This narrative review was conducted to highlight sleep from Islamic perspectives in relation to modern sciences. Method: Selected articles discussing sleep from Islamic perspectives and modern sciences were reviewed and summarized. These articles were retrieved from searches of computerized databases and search engines using keywords “Sleep from Islamic perspective”, “Sleep in modern science”, “Sleep hygiene”, “Western world and sleep”, “Sleep deprivation” and “Quality sleep”. Results: A number of six studies were selected (n=6). Analysis of the results revealed that a productive Muslim sleep routine are divided into three parts; one-third, respectively, for Allah, ourselves and sleep. Sleep hygiene was emphasized and discussed from the Islamic perspectives and the relation with modern sciences: performing ablution and supplicate before sleep, could prepare the body for a deep sleep; dusting the bed before sleep, would get rid of insects that lead to scabies; turning-off lights before sleep to maintain dark environment, could prevent disruption to normal circadian rhythms; early bedtime and early wake-up time, would ensure adequate sleep thus lower the risk of getting chronic diseases; washing the hands after waking-up would get rid of germs accumulated during sleep; and, lying down on the right side is to prevent snoring and to avoid the heart under pressure of the right lung (if lying on the left side). Conclusion: People should not abandon sleep as an important requirement. What have been describes in the Quran and Hadith are corresponded with sleep hygiene as identified by modern sleep scientists. Prophet Muhammad SAW also stressed the importance of sleep for good health and the Quran describe sleep as a blessing from Allah and stresses the importance of the alteration of night and day.